Synthesis and Characterization of Benzo[1,2-b:4,3-b’]dithiophene-Based Biaryls - Valentina Pelliccioli; Luca Ferrari; Francesco Fagnani; Alessia Colombo; Silvia Cauteruccio (Molbank)
The synthesis of three biaryl systems containing the benzo[1,2-b:4,3-b’] framework was accomplished through the Suzuki–Miyaura cross-coupling reaction between 1-bromobenzo[1,2-b:4,3-b’]dithiophene and easily available polycyclic aromatic hydrocarbon boronic acid pinacol esters containing pyrene, fluorene, and fluorenone. The spectroscopic characterization of these molecules was carried out by means of NMR experiments and high-resolution mass spectrometry. UV-vis absorption measurements at different concentrations of the newly synthesized compounds were also performed.